Market Anomaly Analysis: Week Four Effect, Rogalsky Effect and Eid Effect on the IDX 30 Index - Ubed, Nur; Marjohan, Masno; Holiawati, Holiawati (International Journal of Economics, Management and Accounting (IJEMA), 2025)
This study aims to empirically test abnormal returns on the phenomena of the Eid al-Fitr holiday effect, week four effect, rogalsky effect. The research method uses quantitative research. The sampling technique uses the purposive sampling method and daily data samples are obtained. The research sample uses the IDX 30 Stock Index price sourced from the Indonesia Stock Exchange. Data analysis uses the dummy regression method with Wilcoxon Rank. The results of the study show that the Eid al-Fitr Holiday Effect occurred on the IDX 30 IDX Index from 2023 to 2024, which means that the Eid al-Fitr Holiday Effect causes Abnormal Stock Returns on the ID30 IDX Index. The Week Four Effect from 2023 to 2024 did not occur on the IDX30 Index, which means that the Week Four Effect did not affect the ID30 IDX Index Stock Return. Rogalsky Effect from 2023 to 2024 did not occur in the IDX30 Index, which means that the Rogalsky Effect does not affect the IDX30 IDX Index Stock Return.